The Influence of Product Quality, Customer Experience, Price and Brand Image on Purchase Interest - Elinda Putri, Febi; Muslim, Muslim (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Due to the increasingly rapid development of digital marketing or marketing via the internet and social media, it is possible for companies to communicate directly with customers without going through third parties. This research aims to observe the impact of digital marketing communications through word of mouth, which is usually seen by customers through product quality, customer experience, price, brand image through purchase interest which is the hypothesis in this research. Using quantitative methods and using Multiple Linear Regression data analysis with the help of SPSS software. The population in this study includes customers and consumers who have purchased and used products from Scarlett Whitening, using a purposive sampling technique of 88 respondents. Data collection was carried out online by distributing questionnaires in the form of google forms via social media. From the results of this research, it can be concluded that product quality does not have a positive influence on purchase interest, customer experience has a positive influence on purchase interest, price has a positive influence on purchase interest, brand image has a positive influence on purchase interest. This research suggests companies can organize marketing via social media better in order to get maximum results. The coefficient of determination value shows that the variables product quality, customer experience, price, brand image, are able to explain the purchase interest variable by 63.9%, while the remaining 36.1% is explained by other variables outside the model.